Pengaruh Keterlibatan Fesyen, Gaya Hidup Belanja, Emosi Positif, dan Promosi Penjualan terhadap Pembelian Impulsif - Rayhan, Muhammad; Rooswhan Budhi Utomo (Jurnal Bisnis Administrasi dan Manajemen, 2025)
This study aims to analyze the influence of fashion involvement, shopping lifestyle, positive emotion, and sales promotion on impulsive buying behavior at Sumber Rizki Women’s Accessories Store in Bogor. The research applied a quantitative approach with a causal design. Data were collected from 167 respondents using a purposive sampling technique and analyzed with multiple linear regression through SPSS version 30. The results show that fashion involvement and sales promotion have a positive and significant effect on impulsive buying, while shopping lifestyle and positive emotion do not have a significant effect. Simultaneously, the four independent variables significantly influence impulsive buying, with fashion involvement identified as the most dominant factor. The coefficient of determination (Adjusted R²) indicates that the four variables explain 36% of the variation in impulsive buying, while the remaining 64% is influenced by other factors outside this study. These findings highlight the importance of consumer engagement in fashion and attractive sales promotions in stimulating impulsive buying behavior, which can be a strategic reference for businesses in the fashion accessories sector.